Sensoriamento remoto e geofísica aplicados ao reconhecimento lito-estrutural na região de Cabeceiras do Lajeado, São Gabriel - RS - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The constant evolution of knowledge contributes to the development of new tools and techniques for geological mapping. These are increasingly accessible and capable of integrating different products and databases freely available to users. Traditionally, in the previous planning stages for a study, bibliographic analyses are performed. However, there is an under approval of various information, including the vast material of digital sensory data and available information. This work aimed to perform processing, analysis and interpretation of additional public domain data and a terrestrial magnetometric acquisition performed in the western region of the Riograndense Southern Shield in an area between the municipalities of São Gabriel and Santa Margarida do Sul, Rio Grande do Sul state, Brazil. Using remote sensing and geophysical data (aerogamaspectrometry, aeromagnetometry and ground magnetometry), it was possible to generate digital elevation models, geological maps and profiles that integrated allowed important contributions to the regional geological knowledge, proposing new lithological limits. and detailed structural close to an occurrence of Zn-Pb-Cd (Ag). This study provides a methodology that describes organization procedures and routines in a geographic information environment (GIS). Also, serve as an important subsidy for similar approaches. Additionally, the ground geophysical acquisition provides information and results with significant resolution improvements, offering an important complement to studies in the region.
Keywords: Magnetometria; Gamaespectrometria; Ocorrência Mineral; Magnetometry; Gammaspectrometry; Mineral Occurrence; CNPQ::CIENCIAS EXATAS E DA TERRA